The role of bankers in the U.S. syndicated loan market - Herpfer, Christoph (Journal of Accounting and Economics, 2021)
I construct a novel dataset of individual bankers in the U.S. syndicated loan market to analyze the impact of bankers for the largest, most transparent borrowers. Bankers exhibit time-invariant preferences for specific loan characteristics, or styles. In addition, exploiting within-borrower variation in personal relationship strength from banker turnover, I find that stronger relationships lead to significantly lower interest rates. This effect is stronger if borrowers lack a credit rating or issue less frequent and shorter horizon management reports. Relationship loans are associated with fewer bankruptcies and fewer favorable modifications in renegotiations.